P266 D–DIMERO: AN OLD NEGLECTED TEST THAT GOES BEYOND EXPECTATIONS D–DIMER ANALYSIS IN THE STRATIFICATION OF ELDERLY PATIENTS WITH PULMONARY EMBOLISM: EXPERIENCE OF 5 YEARS IN THE EMERGENCY ROOM. (18th May 2022) - Savioli, G; Ceresa, I; Maggioni, P; Novelli, V; Lava, M; Fumoso, F; Lapia, F; Brattoli, M; Bressan, M
Abstract: Purpose: To see if D–Dimer correlates, in the real life of an Emergency Department, with more severe forms of pulmonary embolism (massive pulmonary embolism, presence of organ damage), with the need and duration of hospitalization in resuscitation or the length of hospital stay. We then analyzed correlations with sPESI index, shock indices and blood gas parameters. Methods: Single–center retrospective observational study, on all geriatric patients (> 75) who entered our ED, where they were diagnosed with acute PE. Enrollment began in 2015 and ended in 2019. We collected data from medical history, physical examination, laboratory tests, imaging; we calculated the characteristic scores from the diagnostic / therapeutic algorithm, both for the risk of PE (Wells, Geneva and Anni), and for the presentation of the risk of mortality at 30 days (sPESI). We analyzed all the blood chemistry and blood gas tests performed upon access to the emergency room. We then had all chest CTs retested by an experienced radiologist. We also analyzed vital parameters and the various shock indexes from these derivatives. We then analyzed whether patients had massive pulmonary embolism or the presence of organ damage (right ventricular dilation, pulmonary artery dilation and presence of pulmonary infarction). Results: We enrolled 247 patients, all in need of hospitalization for acute pulmonary embolism. The average age of 83 with female prevalence (62%). High values of D–Dimer show a strong correlation with the presence of massive pulmonary embolism (p < 0.001) and a correlation, albeit to a lesser degree, with the presence of organ damage (p < 0.01). D–Dimer values show a strong correlation (p < 0.005) even with patients at high risk of short–term mortality (presenting right cardiac ventricular dilation and myocardiospecific enzyme elevation). However, the AUC of the ROC curve is not optimal (0.63; with specificity 63% and sensitivity 62%). They also showed a correlation with the need for hospitalization in the ICU (p < 0.01) and a slight correlation with the length of stay in resuscitation (rho = 0.25; p = 0.05) and hospital stay (rho = 0.20; p < 0.01). Conclusions: D–Dimer values appear to be useful in the severity stratification of patients with pulmonary embolism.